Surface Modification of 100% Polyester Plain Woven Fabric by Polyvinyl Alcohol for Enhancing Physical and comfort Properties - Mahbubur Rahman, Tarikul Islam, Md. Rubel Alam, Md. Rezoanur Rahman, Mohaiminul Quayum, Md. Rahidul Islam Saddam (International Journal of Advanced Science and Technology, 2020)
This study attempts to modify the surface of 100% polyester plain woven fabric by polyvinyl alcohol (PVA) for enhancing the physical and comfort properties. The various physical and comfort properties have been evaluated through several test methods such as moisture regain, spray test, water vapor permeability, tensile strength test, abrasion and pilling, crease recovery test. It is seen that moisture regain, spray rating, water vapor permeability and pilling test results were very good to excellent except for tensile strength properties with the increase of PVA concentration. Besides, experiments didn’t indicate any significance improvement on abrasion and crease resistance properties. The result revealed that PVA treated sample’s moisture regain percentage is 3.3 time higher than untreated sample (Treated confirmed by spray rating and water vapor permeability (WVP) test.